Search for large extra dimensions in the production of jets and missing transverse energy in pp collisions at square root of s = 1.96 TeV. - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We present the results of a search for new physics in the jets plus missing transverse energy data sample collected from 368 pb(-1) of pp collisions at square root of s = 1.96 TeV recorded by the Collider Detector at Fermilab. We compare the number of events observed in the data with a data-based estimate of the standard model backgrounds contributing to this signature. We observe no significant excess of events, and we interpret this null result in terms of lower limits on the fundamental Planck scale for a large extra dimensions scenario.